Scalpel, Toxin, and Performance Pressure: Metabolic, Psychiatric, and Psychosocial Aspects of Aesthetic Medicine in Competitive and Physique Athletes - Tsukerman, Jarosław; Szymocha, Joanna; Psiuk, Arkadiusz; Wojas, Aleksandra; Huzarska, Karolina; Baraniecka, Aleksandra; Smędowski, Igor (Quality in Sport, 2026)
Background: The convergence of aesthetic medicine and competitive sport has emerged as a domain of growing clinical concern. Image-driven sponsorship, social-media exposure, and the imperative of peak visual presentation may shape demand for minimally invasive procedures among both endurance- and skill-oriented athletes and physique-oriented competitors such as bodybuilders and fitness athletes. Aim: To synthesise current evidence on metabolic, pharmacokinetic, psychiatric, and psychosocial determinants of aesthetic medicine outcomes in this population and to outline practical recommendations for screening and intervention. Material and Methods: A narrative review of peer-reviewed literature was undertaken across PubMed, Scopus, and Web of Science, prioritising in vivo studies, systematic reviews, meta-analyses, and guidelines issued by psychiatric and dermatological societies. Results: Available data suggest that elevated basal metabolic rate, exercise-induced oxidative stress, and tissue hyperperfusion may shorten the effective duration of crosslinked hyaluronic acid fillers and of botulinum neurotoxin in highly active individuals. Concomitant use of anabolic-androgenic steroids, diuretics, and growth-related peptides may modify wound healing, haemostasis, and filler behaviour. Body dysmorphic disorder, muscle dysmorphia, and disordered eating appear over-represented in physique-oriented sport and may underlie compulsive treatment-seeking. Conclusions: Clinicians treating athletes are encouraged to integrate validated psychometric screening into routine assessment, to anticipate altered pharmacokinetics, and to develop clear psychiatric referral pathways. Prospective trials evaluating filler and neurotoxin durability under sustained physiological stress are warranted.